A Cross-Systematic Review of Addressing Risks in Building Information Modelling-Enabled International Construction Projects - Ganbat, T.; Chong, Heap Yih; Liao, P.; Lee, Cen-Ying (Springer, 2018)
© 2018 CIMNE, Barcelona, Spain. Building information modeling (BIM) is gaining prominence in international construction projects (ICPs). While BIM is able to improve project performance and address certain ICP risks, it can also increase the number of risks to ICPs. This paper aims to provide a comprehensive review for addressing risks in BIM-enabled ICPs. A cross-systematic review approach was adopted to consider limited sources of references when reviewing risks in BIM-enabled ICPs as a single subject. Hence, six steps of reviews were formulated in connection with ICP risks, BIM-related risks, risk analysis and management techniques, and BIM uses. The findings of the cross-systematic review indicate (a) current and potential BIM uses in dealing with ICP risks, and (b) current and potential risk analyses and management techniques in addressing BIM-related risks. The review provides practical references for industry players and valuable insights into the future development of new BIM uses and risk management in BIM-enabled ICPs.